Influence of different application protocols of the universal adhesive system on microleakage of Class V restorations. In vitro study (Research, Society and Development, 2022)
The aim of the present study was to evaluate the influence of different application modes of the universal adhesive system on the marginal microleakage of class V composite resin restorations. For this, 30 bovine incisors were selected, divided into three groups (n=10): Group CT – total etch; Group AC – self-etching and Group CSE – selective enamel etching. The adhesive used was a universal adhesive (Ambar Universal APS, FGM), applied according to the groups. After cavity preparation and application of the adhesive system, they were restored with nanoparticulate composite resin using the incremental technique. After 24 hours, immersed in distilled water, all specimens were prepared and submitted to microleakage test for 24 hours in a 2% methylene blue solution. Then, they were sectioned in the buccolingual direction and evaluated for marginal leakage. The results obtained were submitted to statistical analysis, where no statistically significant difference was observed between the groups. Thus, according to the results of this work, it can be concluded that the universal adhesive can be used in a self-etching form, with no need for pre-conditioning with phosphoric acid.